In-office dental bleaching in adolescents using 6% hydrogen peroxide with and without gingival barrier: a randomized double-blind clinical trial - Carneiro, Taynara de Souza; Favoreto, Michael Willian; Rodrigues, João Pedro Ferreira; Sutil, Elisama; Centenaro, Gabrielle Gomes; Freitas, Isabela de Matos de; Reis, Alessandra; García, Laura Ceballos; Loguercio, Alessandro Dourado (Journal of Applied Oral Science, 2024)
At low concentrations used for in-office bleaching gels, such as 6% HP, gingival barrier continues to be performed. If we take into account that, in the at-home bleaching technique, no barrier is indicated, it seems that the use of a gingival barrier fails to make much sense when bleaching gel in low concentration is used for in-office bleaching. Objective: This double-blind, split-mouth, randomized clinical trial evaluated the gingival irritation (GI) of in-office bleaching using 6% hydrogen peroxide (HP) with and without a gingival barrier in adolescents, as well as color change and the impact of oral condition on quality of life. Methodology: Overall, 60 participants were randomized into which side would or would not receive the gingival barrier. In-office bleaching was performed for 50 minutes with 6% HP in three sessions. The absolute risk and intensity of GI were assessed with a visual analogue scale. Color change was assessed using a digital spectrophotometer and color guides. The impact of oral condition on quality of life was assessed using the Brazilian version of the Oral Health Impact Profile (α=0.05). Results: The proportion of patients who presented GI for the “with barrier” group was 31.6% and for the “without barrier” group, 30% (p=1.0). There is an equivalence for the evaluated groups regarding GI intensity (p<0.01). Color change was detected with no statistical differences (p>0.29). There was a significant impact of oral condition on quality of life after bleaching (p<0.001). Conclusions: The use or not of the gingival barrier for in-office bleaching with 6% HP was equivalent for GI, as well as for bleaching efficacy, with improvement in the impact of oral condition on quality of life.